Boundedness properties of bilinear pseudodifferential operators - Herbert, Jodi (Kansas State University, 2014)
Investigations of pseudodifferential operators are useful in a variety of applications. These include finding solutions or estimates of solutions to certain partial differential equations, studying boundedness properties of commutators and paraproducts, and obtaining fractional Leibniz rules. A pseudodifferential operator is given through integration involving the Fourier transform of the arguments and a function called a symbol. Pseudodifferential operators were first studied in the linear case and results were obtained to advance both the theory and applicability of these operators. More recently, significant progress has been made in the study of bilinear, and more generally multilinear, pseudodifferential operators. Of special interest are boundedness properties of bilinear pseudodifferential operators which have been examined in a variety of function spaces. Since determining factors in the boundedness of these operators are connected to properties of the corresponding symbols, significant effort has been directed at categorizing the symbols according to size and decay conditions as well as at establishing the associated symbolic calculus. One such category, the bilinear Hörmander classes, plays a vital role in results concerning the boundedness of bilinear pseudodifferential operators in the setting of Lebesgue spaces in particular. The new results in this work focus on the study of bilinear pseudodifferential operators with symbols in weighted Besov spaces of product type. Unlike the Hörmander classes, symbols in these Besov spaces are not required to possess in finitely many derivatives satisfying size or decay conditions. Even without this much smoothness, boundedness properties on Lebesgue spaces are obtained for bilinear operators with symbols in certain Besov spaces. Important tools in the proofs of these new results include the demonstration of appropriate estimates and the development of a symbolic calculus for some of the Besov spaces along with duality arguments. In addition to the new boundedness results and as a byproduct of studying operators with symbols in Besov spaces, it is possible to quantify the smoothness of the symbols, in terms of the conditions that define the Hörmander classes, that is sufficient for boundedness of the operators in the context of Lebesgue spaces.
Keywords: Bilinear pseudodifferential operators; Boundedness on Lebesgue spaces; Symbols in Besov spaces; Mathematics (0405)